Hardware and Software of Automated Control System of Plants' Water Well-Being (MCIT: Proceedings of International scientific and practical conference, 2019)
The hardware of the automated control system of plants' water well-being and the software for all components of the system have been developed.
Keywords: hardware; software; automated control system; control unit; mobile application; plants’ water well-being; moisture.